2022
DOI: 10.1002/jbm4.10703
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Alcohol on Bone Health in People Living With HIV: Integrating Clinical Data From Serum Bone Markers With Morphometric Analysis in a Non‐Human Primate Model

Abstract: People living with HIV (PLWH) represent a vulnerable population to adverse musculoskeletal outcomes due to HIV infection, antiretroviral therapy (ART), and at‐risk alcohol use. Developing measures to prevent skeletal degeneration in this group requires a grasp of the relationship between alcohol use and low bone mass in both the PLWH population and its constituents as defined by sex, age, and race. We examined the association of alcohol use with serum biochemical markers of bone health in a diverse cohort of P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 73 publications
0
2
0
Order By: Relevance
“…Furthermore, a prospective cohort study found that higher alcohol intake is significantly associated with lower levels of procollagen type 1 N-terminal propeptide (P1NP), another bone formation biomarker, further confirming the negative impact of alcohol on bone formation in PWH with substance use disorder [70]. Corroborating these findings, another study within the New Orleans Alcohol Use in HIV cohort demonstrated that alcohol use inversely correlates with both osteocalcin and P1NP levels, with these effects being more pronounced in individuals over 50 years of age and in postmenopausal women, highlighting the compounded risk in these subpopulations [71]. Additionally, the study noted positive correlations between serum sclerostin levels and alcohol use, suggesting a potential pathway through which alcohol may exert its osteopenic effects.…”
Section: Smoking and Alcohol Usementioning
confidence: 73%
“…Furthermore, a prospective cohort study found that higher alcohol intake is significantly associated with lower levels of procollagen type 1 N-terminal propeptide (P1NP), another bone formation biomarker, further confirming the negative impact of alcohol on bone formation in PWH with substance use disorder [70]. Corroborating these findings, another study within the New Orleans Alcohol Use in HIV cohort demonstrated that alcohol use inversely correlates with both osteocalcin and P1NP levels, with these effects being more pronounced in individuals over 50 years of age and in postmenopausal women, highlighting the compounded risk in these subpopulations [71]. Additionally, the study noted positive correlations between serum sclerostin levels and alcohol use, suggesting a potential pathway through which alcohol may exert its osteopenic effects.…”
Section: Smoking and Alcohol Usementioning
confidence: 73%
“…Besides sheep, non‐human primates and species like rhesus macaques, Macaca mulatta , or Papio ursinus have been used for bone research. ( 175‐177 ) For ethical reasons, these experiments are not possible in Europe. Several successful approaches highlight the translational potential of these models, for example, in demonstrating that alcohol is a risk factor for osteoporosis after HIV infection.…”
Section: In Vivo Models For Skeletal Research: State Of the Artmentioning
confidence: 99%
“…Several successful approaches highlight the translational potential of these models, for example, in demonstrating that alcohol is a risk factor for osteoporosis after HIV infection. ( 175 ) Non‐human primates have also been used to test biologicals for osteoporosis treatment or fracture healing. ( 178,179 ) Particularly in translational bone research, non‐human primates are the most accurate model in terms of bone metabolism and structure.…”
Section: In Vivo Models For Skeletal Research: State Of the Artmentioning
confidence: 99%